Initial Molecular Response at 3 Months May Predict Both Response and Event-Free Survival at 24 Months in Imatinib-Resistant or -Intolerant Patients With Philadelphia Chromosome-Positive Chronic Myeloid Leukemia in Chronic Phase Treated With Nilotinib - Branford, Susan; Müller, Martin Christian (Journal of clinical oncology, 2012)
Purpose The association between initial molecular response and longer-term outcomes with nilotinib was examined. Patients and Methods Patients with imatinib-resistant or -intolerant chronic myeloid leukemia in chronic phase from the phase II nilotinib registration study with available postbaseline BCR-ABL1 transcript assessments were included (N = 237). Results BCR-ABL1 transcript levels (International Scale [IS]) at 3 months correlated with complete cytogenetic response (CCyR) by 24 months. Patients with BCR-ABL1 (IS) of > 1% to ≤ 10% at 3 months with nilotinib had higher cumulative incidence of CCyR by 24 months than patients with BCR-ABL1 (IS) of > 10% (53% v 16%). BCR-ABL1 (IS) at 3 months predicted major molecular response (MMR) by 24 months. Cumulative incidence of MMR by 24 months for patients with BCR-ABL1 (IS) of > 0.1% to ≤ 1%, > 1% to ≤ 10%, and > 10% was 65%, 27%, and 9%, respectively. These differences were observed for patients with or without baseline BCR-ABL1 mutations and for those with imatinib resistance or intolerance. Estimated event-free survival (EFS) rates at 24 months decreased with higher transcript levels at 3 months; patients with BCR-ABL1 (IS) of ≤ 1% had an estimated 24-month EFS rate of 82%, compared with 70% for patients with BCR-ABL1 (IS) of > 1% to ≤ 10% and 48% for patients with BCR-ABL1 (IS) of > 10%. Conclusion Patients with BCR-ABL1 (IS) of > 10% at 3 months had a lower cumulative incidence of CCyR and MMR and lower rates of EFS versus patients with BCR-ABL1 (IS) of ≤ 10%. Prospective studies may determine whether close monitoring or alternative therapies are warranted for patients with minimal initial molecular response.
Published online ahead of print at www.jco.org on October 29, 2012
Gesehen am 18.06.2018